The effects of different egg yolk concentrations used with soy bean lecithin-based extender on semen quality to freeze bull semen - Serpil Sariozkan; Purhan Barbaros Tuncer; Mustafa Numan Bucak; Serhat Buyukleblebici; Huseyin Kinet; Ali Bilgen (Eurasian Journal of Veterinary Sciences)
Aim: The centrifuged egg yolk (CEY) was added at concentrations of 0.5 or 10% to a defined soy lecithin-based extender (Bioxcell®) used to freeze bull semen and their synergistic effects on post-thaw sperm motility, morphological abnormalities and membrane integrity assessed. Materials and Methods: Ejaculates obtained from each Simmental bull (n:12) divided in three equal aliquots and diluted in CEY 5% (B5), 10% (B10) supplemented, and without any CEY (B0) in soy bean lecithin - based extender, respectively. Thereafter, they were frozen and thawed following a standart protocol. Sperm cryosurvival was evaluated in vitro by microscopic assessments of post-thaw sperm motility (by means of the CASA), acrosomal and other abnormalities (head, mid-pieces, and tail) and plasma membrane integrity (evaluated by HOST). Results: In Simmental bulls, semen extended with B5 had significantly higher CASA motility and CASA progressive motility than those extended with the rest of extenders after freezing and thawing (p<0.001). There was no significant difference in VAP, VCL, and ALH among the three groups (p>0.05). For VSL (p<0.01) and LIN (p< 0.001), the highest values were obtained from B10 group. The highest percentages of acrosomal and other abnormalities were found in semen diluted in B10 (p<0.001). In the group frozen B5, the percentage of membrane integrity was significantly higher than that of the other groups (p<0.001). Conclusion: The use of CEY 5% in combination with soy bean lecithin significantly improved bull semen freezability.